Ethical Considerations in Exploiting, Culturing and Killing Fish towards Animal Rights in Islam - Rahman, M.M; Yunus, Kamaruzzaman; Alenezi, Raslan (IIUM Medical Journal Malaysia, 2018)
Human show cruelty to fish during exploiting, culturing, killing, experimentation and amusement. Presently, overexploitation of marine fishes is a serious problem worldwide. More than 50% of total fish production is now raised in aquafarms where many fish suffer from parasitic infections, diseases, and debilitating injuries in culture systems. Every year, millions of fish are caught in nets and on hooks. Many of them are tortured just for sports. Fishes are also regularly used for scientific experiments. Many of them are killed by unethical ways. Among all animals, human is the main culprits in causing harms to animals including fishes by damaging their ecosystems. To secure animal rights, modern bio-ethics started to be developed in the last century. The principle of modern bio-ethics is very similar to the principle of Islamic bio-ethics. Therefore, modern bio-ethics might be guided by Islamic bio-ethics, which was well established in the 7th century. According to Islam, God gave the human being responsibility to look after animals, to protect them, and not to abuse or threaten them. Human is not permitted to kill animals just for sports or amusements. God created the universe in a perfect balance and human should not disturb this. Therefore, human may exploit and culture food (fish and other organisms) and ornaments without destroying aquatic ecosystems. Islam prescribes a set of rules to treat animals with the utmost kindness and compassion. However, Islamic direction can be integrated with science to ensure minimum stress, pain and suffering when killing animals including fishes.